Genlisea A. St.-Hil. (Lentibulariaceae) of Serra do Cabral State Park, Minas Gerais, Brazil - Guarçoni, Elídio Armando Exposto; Araújo, Ricardo de Souza; Sartori, Marco Aurélio (SITIENTIBUS série Ciências Biológicas, 2007)
This paper consists of the taxonomic study of the genus Genlisea A. St.-Hil. in the municipalities of Buenópolis and Joaquim Felício, Minas Gerais State, Brazil. Four species were identified: G. aurea A. St.-Hil., G. filiformes A. St.-Hil., G. repens Benj., and G. violacea A. St.-Hil. Descriptions, key for identification, illustrations, and comments of these species are provided.